Estimation of Onsite Factors on Polycyclic Aromatic Hydrocarbon Particulate Buildup in Urban Road Networks - Adak, Prasenjit; Elumalai, Suresh Pandian (Frontiers in Environmental Science, 2021)
Soil samples from the urban road and roadside often exhibit a high concentration of polycyclic aromatic hydrocarbons (PAHs). This contamination is attributed to vehicular exhaust emissions. After their release into the atmosphere, the PAH particulate matter eventually is deposited on the road surface and its surrounding areas. In order to develop a theoretical approach to quantify and predict the transport of PAH particulates from the atmosphere to the road soil, the estimation of particulate buildup in the atmosphere is a prerequisite. In the present work, empirical and temporal expressions of particulate buildup in the atmosphere have been developed. The developed site-specific expressions, coupled with other non-site-specific equations can be used for indirect estimation of PAH particulate load in the soil of urban road networks.